The Thermal Analysis Data of the Hydrolysates of the Film-Forming Solutions, Containing Tetraethoxysilane and Mn{2+}, Fe{3+}, Co{2+}, Ni{2+}; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Brichkov A.; Brichkova V.; Egorova L.; Malchik A. G. Aleksandra Gennadievna; Kozik V. V. Vladimir Vasilievich (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen